A BLOCKCHAIN-BASED IPFS AUGMENTED DISTRIBUTED INFORMATION SHARING PARADIGM FOR SECURE COMMUNICATION IN NETWORKED ENVIRONMENT - Muqadsa Jabeen; Majid Hussain; Rana Hassam Ahmed; Hassan Abbas (International Journal of Contemporary Issues in Social Sciences, 2024)
The challenges raised are directly proportional to the progress in data security and information technology. Data sharing, either for internal purposes or across organizations, becomes ever-challenging from the point of view of security. Security aspects are the main problems faced by organizations while communicating data. In spite of the traditional centralized communication systems, there is no answer for the implementation to ensure complete security and privacy. This paper suggests making a truly decentralized communication system for the purpose of sharing information. The aim of this paper is to improve the security and transparency of communication networks using IPFS and blockchain technology, particularly in the aspect of smart contracts. Though the use of blockchain technology is now prevalent in current communication systems, an entirely decentralized messaging network does not exist yet. Communication in the proposed system achieves better cost and latency, with more information shared in real-time without latency. In that system, IPFS, known for its secure and global peer-to-peer (P2P) network, is integrated with the blockchain to allow direct file sharing. We developed this solution in combination with the Ethereum platform and the Solidity programming language.